Takhrij Hadith Itfa’ al-Fatilah: Studi Analisis Takhrij Albani dalam Da’if al-Adab al-Mufrad - Hidayat, Taufiq (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
This article uses content analysis to analyze the quality of gift th about turning off lights while sleeping. The author uses the approach of takhri j simultaneous hadith which starts with analyzing the hadith partially then naqd al-hadith and drawing conclusions. Data sources consist of primary data sources and secondary data sources. Primary data sources in the form of hadith contained in the book of al-Adab al-Mufrad, while secondary data sources come from various kinds of literature such as books, journals and so forth. The purpose of writing this article is to re-analyze the hadith about turning off the lights. The results of the analysis of this paper conclude that hadith about turning off the lights before going to sleep, the history of s aha bat Abu Sa'i d al-Khudhriy who was terminated j by Imam al-Bukhary is h adi th which is da'if al-isnad-sahih al-matn. However, after a simultaneous study, a conclusion was drawn that the hadith is hadih sahih li ghayrih. This conclusion is different from the results of takhrij conducted by al-Albani in Da'if al-Adab al-Mufrad which concluded that the hadith is hadith da’if.